2012
DOI: 10.1308/003588412x13171221498424
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of prognostic scores in decision making and predicting outcomes in metastatic spine disease

Abstract: INTRODUCTION Management of metastatic spinal disease has changed significantly over the last few years. Different prognostic scores are used in clinical practice for predicting survival. The aim of this study was to assess the accuracy of prognostic scores and the role of delayed presentation in predicting the outcome in patients with metastatic spine disease. METHODS Retrospectively, four years of data were collected (2007)(2008)(2009)(2010). Medical records review included type of tumour, duration of symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
(17 reference statements)
2
22
1
Order By: Relevance
“…In our study, the actual survival after surgery was greater than that predicted by the revised Tokuhashi score. This improved survival following surgical intervention was also seen by Majeed et al [13] in their relatively small series of 55 patients. Surgery has a positive impact on improvement in patients' neurological status and Sioutos et al [14] demonstrated that patients who were ambulatory pre-operatively and those with only one vertebral involvement survived statistically longer than patients who were non-ambulatory and with multilevel disease.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study, the actual survival after surgery was greater than that predicted by the revised Tokuhashi score. This improved survival following surgical intervention was also seen by Majeed et al [13] in their relatively small series of 55 patients. Surgery has a positive impact on improvement in patients' neurological status and Sioutos et al [14] demonstrated that patients who were ambulatory pre-operatively and those with only one vertebral involvement survived statistically longer than patients who were non-ambulatory and with multilevel disease.…”
Section: Discussionsupporting
confidence: 76%
“…The revised Tokuhashi score is considered to be a reasonable tool for predicting the prognosis of patients' life expectancy as has been confirmed by numerous authors [8][9][10][11][12][13][14]. In a retrospective review of 246 patients, Tokuhashi and colleagues showed a predictive value of 85.3 % in the group with a score of 0-8, 73.1 % with a score of 9-11 and 95.4 % in the 12-15 group.…”
Section: Discussionmentioning
confidence: 88%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Surgical treatment of spinal metastasis usually involves greater risk of wound infection (2,3,4,5,6,7) compared to other types of spinal surgery. The risk factors for wound infection in these patients are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Leithner et al 20 proposed the inclusion of multiple myeloma among the malignancies with longer survival times, despite its being a hematological disease rather than a metastatic disease spread from a solid tumor, and suggested that these patients be included in a group with a better prognosis. Thus, in the Tokuhashi score, the primary site would receive 5 points, and in the Tomita score, a classification as a slow-growing primary site would receive 1 point.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the Tokuhashi score, the primary site would receive 5 points, and in the Tomita score, a classification as a slow-growing primary site would receive 1 point. The study by Majeed et al 21 also included patients with myeloma in the Tokuhashi and Tomita scores, given that they are allocated to the same category as patients with metastasis of the prostate and breast and because a similar survival was observed in the study by these authors. In our study we observed great variability in our attempt to include myeloma in these scores.…”
Section: Discussionmentioning
confidence: 99%